Political Representation and Citizenship in Portugal: from Crisis to Renewal? - Lisi, M.; Marco Lisi; Freire, A.; Tsatsanis, E.; Emmanouil Tsatsanis (2020)
Marco Lisi, André Freire & Emmanouil Tsatsanis (editors) (2020), Political Representation and Citizenship in Portugal: from Crisis to Renewal, Lexington Books – Rowman & Littlefield, 2020.